Where will you setup your business next?: a machine learning approach to suggest ideal geographical location for new restaurant establishment - Shihab, Ibne Farabi; Oishi, Maliha Moonwara (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.